There and back again: dynamics of temporary labor migration, insights from rural India - Attah-Otu, Bernard; Sengupta, Angan; McAleavy, Tony (Frontiers in Sociology, 2024)
Temporary labor migration is a household phenomenon among rural communities in India. This study seeks to understand the subjective experiences influencing the temporariness of labor migration among internal migrants in India by examining various factors such as migration conditions, motivation, migration arrangements, coping and adaptation strategies, and determinants of stay. To achieve this objective, the current qualitative study utilized 14 in-depth interviews and 2 focus group discussions to investigate the temporary nature of labor migration among internal migrants in India. Our findings reveal that migration decisions are rational choices made collectively at the household level, considering socio-economic outcomes. We also find that social networks and contractors facilitate migration arrangements and job connections, and migrants employ various strategies to reduce costs and cope with expenses in urban areas. However, migration destinations often fail to meet migrants’ expectations, exposing them to low-wage employment and precarious working and living conditions, which are detrimental to their health. Limited housing and sanitation facilities further contribute to the challenges faced by migrants. Work conditions, including poor wages and high job demands, also affect their well-being. These findings highlight the need for improved support systems that address accommodation challenges, work conditions, and the overall welfare of labor migrants.